An Analysis of the Moral Crisis of Children towards Parents, Teachers, and Community in the 21st Century - Julkifli Julkifli; Mardianto Mardianto (Jurnal Basicedu, 2022)
The sophistication of technology with its various alternative conveniences, has a significant impact on the moral crisis among children, especially at the elementary age level (SD/MI). This study aims to analyze the moral crisis of elementary age students, with a research background (case study) in Tambak Cekur Village, Serbajadi District. The focus of this research is how the moral crisis occurs among elementary age children, as well as the role of parents, teachers, and society in responding to it. This type of research uses a qualitative approach with analytical descriptive study methods. Data collection was carried out using in-depth interviews, participant observation, and documentation studies. Furthermore, the data were analyzed using reduction techniques (data sorting), data presentation, and drawing conclusions. The results of this study found that the use of gadgets without parental supervision causes a massive moral crisis among elementary age children. In addition to playing online games, children are also affected by various shows that are negligent, so that the "golden age" for children to learn becomes negligent by imitating more "style" dances with tiktok applications and video snacks than studying. Through this research, it is hoped that it can become a basic concept for parents to present their role as educators in the family environment for children and supervise children from various negative impacts caused by the use of smartphones.